2020
DOI: 10.3390/en13020332
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Novel Magnetic Coupler of an In-Wheel Wireless Power Transfer System for Electric Vehicles

Abstract: Electric vehicle (EVs), which use an electric motor, are expected to replace internal combustion engine vehicles. However, to date EVs are not highly attractive to consumers due to their unsatisfactory battery charging characteristics and high cost. In particular, the existing conductive charging method makes it more difficult to spread EVs due to the inconvenience of charging and the risk of electric shock. The wireless power transfer (WPT) system can eliminate all of the charging troubles of EVs. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The WPT is a method that transfers the energy between transmitting and receiving coil based on some resonant conditions 6 . The wireless charging operation for EV is carried out in stationary or dynamic mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WPT is a method that transfers the energy between transmitting and receiving coil based on some resonant conditions 6 . The wireless charging operation for EV is carried out in stationary or dynamic mode.…”
Section: Introductionmentioning
confidence: 99%
“…5 The WPT is a method that transfers the energy between transmitting and receiving coil based on some resonant conditions. 6 The wireless charging operation for EV is carried out in stationary or dynamic mode. Initially, the vehicle is parked whereby transmitting the coil is parallel to the receiving coil in the first mode.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been devoted to maximizing PTE with regards to the mentioned three impacting factors (i.e., K , Q i -, and Q L -factors). This article focuses on geometric optimization of Tx/Rx coil pairs as a means of improving inductive linkage [1], [5]- [9], [14], [15], [23]- [32], which can additionally reduce the IPT system's physical size. One of the methods for geometric optimization of inductive coils is through increasing Q i -factor of the Tx/Rx coil pairs which has been considered by many researchers including [24]- [27].…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the system's overall PTE through coil geometry optimization, different iterative design algorithms have been proposed over the last few decades [1], [5]- [7], [9], [14], [15], [28]- [32]. As a common approach to cancel out the loading effect of Tx/Rx terminating circuitry, Jow and Ghovanloo [1], Ibrahim and Kiani [5], Sallan et al [9], Hwang and Jang [15], Ko et al [29], and Donaldson and Perkins [30] have found equations for PTE based on the system parameters (e.g., K , R s , R L , etc.). Then, for the derived PTE equation, various figure-of-merit (FoM) parameters are defined to help improve energy transmission efficiency for the purpose application.…”
Section: Introductionmentioning
confidence: 99%
“…
Asynchronous permanent magnet coupling can transmit torque without any physical contact,it has a series of advantages such as no friction, vibration isolation, simple installation, overload protection and so on (Wallace and Jouanne, 2001; Dave et al,2013), the application fields include power transmission, petroleum, chemical industry, pharmacy, etc (Hwang and Jang, 2020;Zhu, 2014). And by adjusting the magnetic field coupling length, asynchronous magnetic coupler can control slip speed, so that it also has functions of Soft Start and stepless speed regulation, which can replace frequency converter under certain conditions (Wang et al, 2019;Mohammadi and Mirsalim, 2019), so it also has broad development potential in the field of energy conservation (Zhao et al,2010;Duan and Wang, 2012).
…”
mentioning
confidence: 99%